The Paradox of Akt-mTOR Interactions - VADLAKONDA, LAKSHMIPATHI; Dash, Abhinandita; Pasupuleti, Mukesh; Kotha, Anil Kumar; Reddanna, Pallu (Frontiers in Oncology, 2013)
The serine threonine (ser/thr) protein kinase, Akt, is at the central hub of signaling pathways that regulates cell growth, differentiation and survival. The reciprocal relation that exists between the two activating phosphorylation sites of Akt, T308 and S473, and the two mTOR complexes, C1 and C2, forms the central controlling hub that regulates these cellular functions. In our previous review 'PI3K-AKT-mTOR and Wnt signaling pathways in cell cycle' we discussed the reciprocal relation between mTORC1 and C2 complexes in regulating cell metabolism and cell cycle progression in cancer cells. We present in this article, a hypothesis that activation of Akt T308 phosphorylation in the presence of high ATP: AMP ratio promotes the stability of its phosphorylations and activates mTORC1 and the energy consuming biosynthetic processes. Depletion of energy leads to inactivation of mTORC1, activation of AMPK, FoxO, and promotes constitution of mTORC2 that leads to phosphorylation of Akt S473. Akt can also be activated independent of PI3K; this appears to have an advantage under situations like dietary restrictions, where IIS could be a casualty.